2017
DOI: 10.1016/j.addbeh.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Measures and predictors of varenicline adherence in the treatment of nicotine dependence

Abstract: Introduction While adherence to medication in smoking cessation clinical trials is strongly associated with clinical outcome, very few studies have evaluated the validity of pill count as a measure of adherence relative to a biological assay, and evaluated a broad range of correlates of adherence. Methods In a smoking cessation clinical trial of varenicline, we compared pill counts collected over 4 different time periods to varenicline salivary levels taken after 2 weeks of treatment, as well as evaluated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 47 publications
4
38
2
Order By: Relevance
“…Varenicline is one of the most effective medications for tobacco dependence ( Cahill, Stevens, Perera, & Lancaster, 2013 ) even among smokers with psychiatric ( Anthenelli et al, 2016 ) and medical ( Price et al, 2017 ) comorbidities. However, in general population clinical trials, adherence to varenicline rarely exceeds 60% (e.g., Peng et al, 2017 ), with little known about adherence rates in populations with comorbidities ( Pacek, McClernon, & Bosworth, 2017 ). Across numerous studies, suboptimal adherence significantly reduces the likelihood of successful quitting ( Pacek et al, 2017 ; Peng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varenicline is one of the most effective medications for tobacco dependence ( Cahill, Stevens, Perera, & Lancaster, 2013 ) even among smokers with psychiatric ( Anthenelli et al, 2016 ) and medical ( Price et al, 2017 ) comorbidities. However, in general population clinical trials, adherence to varenicline rarely exceeds 60% (e.g., Peng et al, 2017 ), with little known about adherence rates in populations with comorbidities ( Pacek, McClernon, & Bosworth, 2017 ). Across numerous studies, suboptimal adherence significantly reduces the likelihood of successful quitting ( Pacek et al, 2017 ; Peng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous clinical studies of varenicline, the literature has relied upon self-reported pill count data to determine varenicline adherence with only two exceptions ( Buchanan et al, 2012 ; Peng et al, 2017 ). Unfortunately, self-reported pill count data are susceptible to response bias and misreporting, which can overestimate adherence ( Dunbar-Jacob & Rohay, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is one of the largest smoking cessation trials conducted with cancer patients. Lastly, adherence to varenicline was low, even vs the general population where it is typically 50% to 60% . With more than half the sample taking less than 80% of the prescribed medication, the therapeutic effect of varenicline was limited, which may have diminished long‐term cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, adherence to varenicline was low, even vs the general population where it is typically 50% to 60%. 39,40 With more than half the sample taking less than 80% of the prescribed medication, the therapeutic effect of varenicline was limited, which may have diminished long-term cessation. The complexity and intensity of ongoing medical care for patients may have posed particular challenges for treatment engagement and future studies are needed to develop and test novel approaches for increasing treatment adherence.…”
Section: Limitationsmentioning
confidence: 99%
“…Nausea severity data were collected through self-report at multiple time-points in the Quit2Live (weeks 1, 4 and 8) and PNAT (weeks 1 and 2) trials; nausea was examined on a 4-point scale (0-3), as previously described in varenicline randomized clinical trials [17][18][19][20][21][22][23][24][25][26]. Adherence was biologically assessed at weeks 4 (Quit2Live, plasma sample) and 2 (PNAT, saliva sample) using varenicline concentrations analyzed by LC-MS/MS (limit of quantification = 0.05 ng/ml for plasma, 1 ng/ml for saliva) [6,27,28]. Adherence was determined based on varenicline concentrations instead of self-report pill counts, as the varenicline concentrations were more predictive of cessation outcomes, while self-report pill counts tended to over-estimate adherence and were less predictive of cessation outcomes [6,7,29].…”
Section: Nausea and Varenicline Adherence Assessmentmentioning
confidence: 99%